Neutrophilic infiltration within the airway smooth muscle in patients with COPD. Issue 4 (26th March 2004) - Baraldo, S; Turato, G; Badin, C; Bazzan, E; Beghé, B; Zuin, R; Calabrese, F; Casoni, G; Maestrelli, P; Papi, A; Fabbri, L M; Saetta, M
Abstract : Background: COPD is an inflammatory disorder characterised by chronic airflow limitation, but the extent to which airway inflammation is related to functional abnormalities is still uncertain. The interaction between inflammatory cells and airway smooth muscle may have a crucial role. Methods: To investigate the microlocalisation of inflammatory cells within the airway smooth muscle in COPD, surgical specimens obtained from 26 subjects undergoing thoracotomy (eight smokers with COPD, 10 smokers with normal lung function, and eight non-smoking controls) were examined. Immunohistochemical analysis was used to quantify the number of neutrophils, macrophages, mast cells, CD4+ and CD8+ cells localised within the smooth muscle of peripheral airways. Results: Smokers with COPD had an increased number of neutrophils and CD8+ cells in the airway smooth muscle compared with non-smokers. Smokers with normal lung function also had a neutrophilic infiltration in the airway smooth muscle, but to a lesser extent. When all the subjects were analysed as one group, neutrophilic infiltration was inversely related to forced expiratory volume in 1 second (% predicted). Conclusions: Microlocalisation of neutrophils and CD8+ cells in the airway smooth muscle in smokers with COPD suggests a possible role for these cells in the pathogenesis of smoking induced airflow limitation.